Elucidation of in situ polycyclic aromatic hydrocarbon degradation by functional metaproteomics (protein‐SIP). Issue 18 (18th June 2013) - Herbst, Florian‐Alexander; Bahr, Arne; Duarte, Marcia; Pieper, Dietmar H.; Richnow, Hans‐Hermann; von, Martin; Seifert, Jana; Bombach, Petra; Rabus, Ralf
<x xml:space="preserve">Abstract</x> Current knowledge of the physiology and phylogeny of polycyclic aromatic hydrocarbon (PAH) degrading bacteria often relies on laboratory enrichments and isolations. In the present study, in situ microcosms consisting of activated carbon pellets (BACTRAP®s) were loaded with either 13C‐naphthalene or 13C‐fluorene and were subsequently exposed in the contaminant source and plume fringe region of a PAH‐contaminated aquifer. Metaproteomic analysis and protein‐stable isotope probing revealed Burkholderiales, Actinomycetales, and Rhizobiales as the most active microorganisms in the groundwater communities. Proteins identified of the naphthalene degradation pathway showed a relative 13C isotope abundance of approximately 50 atom% demonstrating that the identified naphthalene‐degrading bacteria gained at least 80% of their carbon by PAH degradation. Although the microbial community grown on the fluorene‐BACTRAPs showed a structure similar to the naphthalene‐BACTRAPs, the identification of fluorene degraders and degradation pathways failed in situ. In complementary laboratory microcosms, a clear enrichment in proteins related to Rhodococcus and possible fluorene degradation enzymes was observed. This result demonstrates the impact of laboratory conditions on microbial community structure and activity of certain species and underlines the need on in situ exploration of microbial community functions. In situ microcosms in combination with protein‐stable isotope probing may be a significant tool for in situ identification of metabolic key players as well as degradation pathways.